A gestão social das racionalidades produtivas dos agricultores familiares nas mesorregiões oeste e centro ocidental paranaense - Pavinato, Julie Mathilda Semiguem (2022)
This thesis aims to analyze social management in the different rationalities existing in family farming in the northwest and western regions of Paraná. To contextualize the research theme, we discuss the rationality that is approached from weber's concepts (1992;1994); Guerreiro Ramos (1981;1983); Leff (1993) and Habermas (1987, 1990); to define and describe the set of meanings and motivations that lead the actors towards their decisions; definitions are presented on family agriculture, instrumental rationalities, substantive, management, management in family units, social management and interfaces with Sustainable Rural Development. The study sought to answer the question: what are the rationalities observed in the practice of social management among family farmers that allow the emergence of diversity among them? To answer this question, the study was exploratory without considering the evolution of the data over time. The participants were the thirty-five family farmers from the west and northwest regions of Paraná. The data collection instrument was a questionnaire using the Basso typology (2013) to classify the producers into three types, as being: type 1 - Conventional; Type 2 - in transition and type 3 - unconventional. The conventional type has objectives aimed at producing for the market and making investments for improvements in the production area of the production unit, demonstrating a strong interaction with the market, totaling thirty-four questions. The conventional type has objectives aimed at producing for the market and making investments for improvements in the production area of the production unit, demonstrating a strong interaction with the market. The profit conception of this type of farmer is connected to the efficiency of its production process. The rationalities diagnosed in the social management practices of this type of farmer approach the substantive rationality in the bonds with the community and instrumental in its decision-making process regarding the productive system. Type 2 – in Transition (hybrid) brings in its management practices a mixture of characteristics that encompass conceptions of the other two types, to appropriate the strategies that benefit its production unit. It is of the most difficult types to classify, precisely because of this ambiguity (sometimes focused on the market/ or for social values). The unconventional type 3 social management practices make clear the importance of the family in the decisions and action of work in the family production unit. The objectives of these management practices seek to ensure the survival of the family and the actions aim at diversified production for domestic consumption. This type of farmer has a particular understanding of profit since he thinks about production from the health benefits and quality of life of the family. The results of the research indicate that instrumental, multifaceted, and substantive rationalities support the decision-making choices in the process of social management of their property and their worldview. And, they are articulated in an interdisciplinary way and are not fixed, but changeable in view of the environmental, regional, and individual context.